2016
DOI: 10.1002/ptr.5711
|View full text |Cite
|
Sign up to set email alerts
|

Germacrone Inhibits Estrogen Receptor α‐Mediated Transcription in MCF‐7 Breast Cancer Cells

Abstract: Estrogen receptor (ER)α-positive breast cancer cells regulate the expression of estrogen-responsive genes, which are involved in cell proliferation, differentiation, and cell cycle progression. Clinically, the inhibition of ERα-mediated gene expression in breast cancer cells has long been considered an effective way to prevent the development and progression of cancer. Germacrone, a terpenoid compound isolated from Rhizoma curcuma, has been known to have antitumor activity in various human cancer cell lines. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Recent studies have found that germacrone has a significant anti-cancer effect, can inhibit the progress of colorectal cancer, liver cancer, breast cancer, lung cancer and other cancers, and has the characteristics of high efficiency and low toxicity [18][19][20]. Lim et al found that germacrone inhibited breast cancer progression by inhibiting estrogen receptor α and synergizing with other antitumor drugs 5-fluorouracil and methotrexate [21]. However, there are relatively few studies on the neuroprotective effects of germacrone.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that germacrone has a significant anti-cancer effect, can inhibit the progress of colorectal cancer, liver cancer, breast cancer, lung cancer and other cancers, and has the characteristics of high efficiency and low toxicity [18][19][20]. Lim et al found that germacrone inhibited breast cancer progression by inhibiting estrogen receptor α and synergizing with other antitumor drugs 5-fluorouracil and methotrexate [21]. However, there are relatively few studies on the neuroprotective effects of germacrone.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative treatment for breast cancer, ingredients isolated from natural products have been extensively investigated. In our previous study, we showed that germacrone inhibits the proliferation and migration of MCF-7 breast cancer cells 5 by the inhibition of ERα signaling 24 . The expressions of the anti-apoptotic Bcl-2 and Bcl-xL protein and the pro-apoptotic TP53 and TP21 were dose-dependently regulated by germacrone as well 25 27 .…”
Section: Discussionmentioning
confidence: 98%
“…Germacrone is a monocyclic sesquiterpene extracted from gingeraceae plants with antitumor, anticancer, antiviral, antibacterial, and anti-inflammatory activity [16][17][18]. In particular, germacrone antitumor effect on the human hepatoma cell line is mediated via G2/M cell cycle arrest and by promoting apoptosis [19].…”
Section: Introductionmentioning
confidence: 99%